Analysis by rotavirus gene 6 reverse transcriptase-polymerase chain reaction assay of rotavirus-positive gastroenteritis cases observed during the vaccination phase of the Rotavirus Efficacy and Safety Trial (REST) - Matson, David O; Vesikari, Timo; Dennehy, Penelope; Dallas, Michael D; Goveia, Michelle G; Itzler, Robbin F; Ciarlet, Max (Human vaccines & immunotherapeutics, 2014)
During the vaccination phase of the Rotavirus Efficacy and Safety Trial (REST), the period between the administration of dose 1 through 13 days after the administration of dose 3, there were more wild-type rotavirus gastroenteritis (RVGE) cases among vaccine recipients compared with placebo recipients using the protocol-specified microbiological plaque assay in the clinical-efficacy cohort, a subset of subjects where vaccine efficacy against RVGE of any severity was assessed. In this study, a rotavirus genome segment 6-based reverse transcriptase-polymerase chain reaction assay was applied post hoc to clarify the accuracy of type categorization of all these RVGE cases in vaccine recipients during the vaccination phase of REST. The assay characterized 147 (90%) of 163 re-assayed RVGE cases or rotavirus-associated health care contacts as type-determinable: either wild-type or vaccine-type rotavirus strains. In the clinical-efficacy cohort (N = 5673), 19 (18.8%) of 101 samples from RVGE cases contained wild-type rotavirus, 70 (69.3%) vaccine virus, and 12 (11.9%) were indeterminable. In the large-scale cohort (N = 68,038), 10 (34.5%) of 29 samples from RVGE-related health care contacts contained wild-type rotavirus strains, 15 (51.7%) vaccine-type rotavirus strains, and 4 (13.8%) were indeterminable. Of the 33 samples from RVGE cases in placebo recipients, all were confirmed to contain wild-type rotaviruses. Altogether, this post-hoc re-evaluation showed that the majority (75%) of type-determinable RVGE cases or health care contacts that occurred during the vaccination phase of REST in vaccine recipients were associated with vaccine-type rotavirus strains rather than wild-type rotavirus strains.